Implementasi Alat Peraga Jari Trigonometri untuk Meningkatkan Hasil Belajar Trigonometri Siswa SMA - Gusasi, Moh Akbar; Abbas, Nurhayati; Zakaria, Perry (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
This study aims to improve students’ mathematics learning outcomes on trigonometry material through the use of trigonometric finger teaching aids. The study employed a classroom action research approach conducted at SMA Negeri 1 Kabila in the 2024/2025 academic year. The research subjects were 38 students of class X-9. The research was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through learning outcome tests and observations of teacher and student activities. Data analysis was conducted using descriptive quantitative techniques based on percentages. The results showed an increase in students’ learning mastery from 36.8% in Cycle I to 81.6% in Cycle II. Teacher and student activities also improved and reached very good criteria. These findings indicate that trigonometric finger teaching aids are effective in improving students’ learning outcomes in trigonometry.